Effects of Ketamine and Xylazine-Ketamine Combination in Clinical and Haemato-biochemical Parameters in Captive Rhesus Monkey (Macaca mulatta) (Nepalese Veterinary Journal, 2018)
This study was carried to compare the effects of ketamine and xylazine-ketamine combination on clinical and haematobiochemical parameters in captive rhesus monkey. The animals were divided into two groups; one ketamine (K) group and other xylazine-ketamine (XK) group. In ketamine group (n=6) atropine sulphate and ketamine was used intramuscularly at the rate of 0.04 mg/kg body weight and 10 mg/ kg body weight respectively. In xylazine-ketamine group (n=3) xylazine and ketamine was used intramuscularly at the rate of 1 mg/kg body weight and 5 mg/kg body weight respectively. Blood samples were collected immediately after induction and 30 min after induction in both groups. Effects of anaesthetics on haematological and biochemical parameters such as TEC, TLC, Hb, PCV, DLC, serum cholesterol, serum triglyceride, HDL and LDL and clinical parameters such as rectal temperature, heart rate, respiration rate, muscle relaxation, jaw tone, pedal reflex, palpebral reflex and position of eye ball were studied. Rectal temperature was significantly lower (P0.05). Lymphocyte was lower in group XK than in group K but it was nonsignificant (P>0.05). Monocyte was significantly lower (P0.05). Serum triglyceride and LDL was significantly higher (P0.05). Smooth induction was found in group XK and duration of anaesthesia was longer in group XK whereas smooth recovery was found in group K but duration of anaesthesia was shorter. Muscle relaxation was excellent in group XK in comparison to group K. It can be suggested from the results of this study that for shorter duration of anaesthesia only ketamine can be used but for longer duration, xylazine-ketamine combination will be appropriate.